HUBUNGAN ANTARA SELBSVERTRAUEN DAN SPRECHFERTIGKEIT BAHASA JERMAN SISWA KELAS XI SMA NEGERI 8 MAKASSAR - Nurlina, Nurlina; R., Mantasiah; Azizah, Laelah (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. This research was conducted to obtain data and information about the relationship between Selbsvertrauen and Sprechfertigkeit German Language Class XI students of SMA Negeri 8 Makassar. The variable in this study is Selbsvertrauen and the dependent variable is Sprechfertikgeit. The population in this study were all class XI of SMA Negeri 8 Makassar consisting of 3 classes, the sample in this study were students of class XI MIPA 2 at SMA Negeri 8 Makassar with a total of 35 people. The results of this study obtained the results of speaking skills and questionnaire tests. Based on the results of the study indicate that the R count is greater than the R table (0.796 <0.334). The analysis showed that there was a relation between Selbsvertrauen and Sprechfertigkeit German Language Class XI students at SMA Negeri 8 Makassar.